Evolutionary competition and profit taxes: market stability versus tax burden - Noemi Schmitt; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
The seminal cobweb model by Brock and Hommes reveals that fixed-point dynamics may turn into increasingly complex dynamics as firms switch more quickly between competing expectation rules. While policy-makers may be able to manage such rational routes to randomness by imposing a proportional profit tax, the stability-ensuring tax rate may cause a very high tax burden for firms. Using a mix of analytical and numerical tools, we show that a rather small profit-dependent lump-sum tax may even be sufficient to take away the competitive edge of cheap destabilizing expectation rules, thereby contributing to market stability.
Keywords: D84; E30; Q11; 330; cobweb models; discrete choice approach; intensity of choice; profit taxes; tax burden; stability analysis